Application of the FMECA method for identifying failures in wind turbine systems - Radišić, Branislava (Vojnotehnički glasnik / Military Technical Courier, 2026)
This paper presents the potential causes of component failures in wind turbine systems that affect their reliable and efficient operation. Component failures in wind turbines can lead to complete system failure, resulting in downtime, reduced reliability, and increased costs. To fully utilize wind energy, minimizing the risk of component failures is essential. By applying the FMECA method (Failure Mode Effects and Criticality Analysis – FMECA), critical components of wind turbine systems have been identified, providing the opportunity to prioritize problem-solving. The results emphasize the importance of maintenance and design optimization to reduce the risk of failures and maximize the utilization of wind energy. Introduction/purpose: The reliability of wind turbine systems plays a crucial role in ensuring a stable and efficient electricity supply from renewable sources. The failure of any component can lead to system downtime, reduced reliability, and increased operational costs. In this context, it is essential to identify and analyze potential failures in order to improve overall system reliability. The aim of this paper is to analyze the reliability of a wind turbine system using the FMECA method. The focus is on identifying the most critical components and understanding the causes and consequences of their failures, thereby contributing to the improvement of system design, maintenance, and operation. Methods: This paper applies the FMECA (Failure Modes, Effects, and Criticality Analysis) method, which enables a detailed assessment of potential system failures, their causes and effects, and the identification of the most critical system points based on quantitative parameters. The methodology includes the following steps: · Identification of key components of the wind turbine, including the rotor, gearbox, generator, control system, and other subsystems. · Definition of possible failure modes for each component, with corresponding mechanisms that may lead to failure (e.g., wear, overheating, mechanical damage, etc.). · Evaluation of the consequences of failures, both on the specific component and on the overall operation of the wind turbine. · Quantitative risk assessment through the assignment of values for: o the probability of potential failure occurrence (R1), o the severity of the potential failure (R2), and o the probability of detecting the failure and preventing its manifestation (R3). · Calculation of the criticality level (R) using the expression: · Ranking of components based on R values to identify those that pose the greatest threat to system reliability and require prioritized monitoring or optimization. Results: The results of the FMECA analysis indicate that the most critical components of the wind turbine system are: 1. Gearbox – the highest criticality level (R value), as gearbox failure can lead to complete system shutdown and costly repairs. 2. Generator – high severity of failure and moderate likelihood of failure detection. 3. Wind turbine control system – although failures are less frequent, the consequences can be severe due to the loss of control over the turbine. Based on the analysis, components have been classified according to maintenance and monitoring priorities to enable timely detection of potential failures and prevent major breakdowns. Conclusion: The FMECA method has proven to be an effective tool for identifying and ranking potentially critical components of wind turbine systems. The results indicate that the gearbox, generator, and control system are the most sensitive points in the system. Their preventive maintenance, along with the implementation of condition monitoring systems and design improvements, can significantly enhance reliability and reduce operational costs. This analysis can serve as a foundation for improving maintenance strategies and increasing the operational efficiency of wind farms.